PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Natalia Sutanto; I Gede Siswantaya (Modus, 2014)
The purpose of this study is to test empirically the relationship between intellectual capital and frm performance. Intellectual capital is measured using the method Pulic namely value added intellectual coefcient (value added intellectual coefcient-VAICTM) as a measure of the efciency of venture capital and intellectual capital. The companyâ€™s performance is measured using four indicators, namely ROA, ATO, ROE, and MB. Te sample used by 27 companies listed banking sector in Indonesia Stock Exchange f rom 2007 until 2012. Data analysis too lused to test the hypothesis is Partial least square (PLS). Hypothesis test results show evidence that intellectual capital and signifcant positive efect on company performance and future performance of the company. For the rate of growth in intellectual capital (ROGIC) did not signifcantly afect the future performance of the company.Keywords:Â intellectual capital, company performance, Partial Least Square (PLS)